Ixabepilone alone or with cetuximab as first-line treatment for advanced/metastatic triple-negative breast cancer - Trédan, Olivier; Campone, Mario; Jassem, Jacek; Vyzula, Rostislav; Coudert, Bruno; Pacilio, Carmen; Prausova, Jana; Hardy-Bessard, Anne-Claire; Arance, Ana; Mukhopadhyay, Pralay; Aloe, Alessandra; Roché, Henri (Clinical breast cancer, 2015)
BACKGROUND: Despite high initial sensitivity to chemotherapy, TNBC is associated with a poor prognosis, highlighting the need for novel therapeutic strategies. The aim of this multicenter, randomized, open-label phase II trial was to assess the efficacy of ixabepilone as monotherapy, and the combination of ixabepilone with cetuximab, as first-line treatment in patients with triple-negative locally advanced nonresectable and/or metastatic breast cancer. PATIENTS AND METHODS: Women were randomly assigned to receive either ixabepilone (40 mg/m(2)) every 21 days (n = 40), or ixabepilone (40 mg/m(2)) every 21 days with cetuximab (400 mg/m(2) loading dose, followed by 250 mg/m(2)) once weekly (n = 39). The primary end point of the trial was to estimate the response rates of ixabepilone monotherapy and ixabepilone with cetuximab combination therapy. RESULTS: Of 79 randomized patients, 77 were treated. Based on an intent-to-treat analysis, an objective response rate of 30% (95% confidence interval [CI], 16.6-46.5) was observed in the monotherapy arm, and 35.9% (95% CI, 21.2-52.8) in the combination arm. Median progression-free survival was 4.1 months in both treatment groups. Safety findings were consistent with the known individual toxicity profiles of ixabepilone and cetuximab. Skin and subcutaneous tissue disorders were more common with combination therapy, as were discontinuations because of adverse events. CONCLUSION: Ixabepilone monotherapy and the ixabepilone and cetuximab combination demonstrated similar levels of clinical activity in first-line treatment of advanced TNBC, with a predictable safety profile. Further investigation of novel therapies for TNBC is required to improve patient outcomes.
Keywords: senioři; metastázy nádorů; Neoadjuvant Therapy; Metastatic breast cancer; Disease Progression; triple-negativní karcinom prsu; progrese nemoci; Ixabepilone; výsledek terapie; Triple Negative Breast Neoplasms; Middle Aged; cetuximab; adenokarcinom; EGFR; Adult; Epothilones; Neoplasm Metastasis; Disease-Free Survival; ženské pohlaví; Humans; Triple negative; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; epothilony; neoadjuvantní terapie; lidé středního věku; Cetuximab; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; dospělí; Female; Aged; Treatment Outcome; Adenocarcinoma; přežití bez známek nemoci; lidé